The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1038/s41388-023-02611-y
|View full text |Cite|
|
Sign up to set email alerts
|

Transgenic IDH2R172K and IDH2R140Q zebrafish models recapitulated features of human acute myeloid leukemia

Abstract: Isocitrate dehydrogenase 2 (IDH2) mutations occur in more than 15% of cytogenetically normal acute myeloid leukemia (CN-AML) but comparative studies of their roles in leukemogenesis have been scarce. We generated zebrafish models of IDH2R172K and IDH2R140Q AML and reported their pathologic, functional and transcriptomic features and therapeutic responses to target therapies. Transgenic embryos co-expressing FLT3ITD and IDH2 mutations showed accentuation of myelopoiesis. As these embryos were raised to adulthoo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Interactions between Pink1 and other candidate proteins, such as TP16, TP53, BECN, and RAC1 warrants further investigation. Nevertheless, with the advancement of zebrafish modelling in hematopoiesis and leukemia 38,39 , our study demonstrated the potential of zebrafish model to further investigate the novel role of Pink1 in vertebrate autophagy and hematopoiesis in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…Interactions between Pink1 and other candidate proteins, such as TP16, TP53, BECN, and RAC1 warrants further investigation. Nevertheless, with the advancement of zebrafish modelling in hematopoiesis and leukemia 38,39 , our study demonstrated the potential of zebrafish model to further investigate the novel role of Pink1 in vertebrate autophagy and hematopoiesis in vivo.…”
Section: Discussionmentioning
confidence: 90%
“…Combination therapy decreased DNA methylation even more than the monotherapy [ 215 ]. FLT3-ITD and IDH2 R172K or IDH2 R140Q double mutated zebrafish model, when treated with quizartinib and enasidenib, showed reduction in the blast population and spleen size [ 226 ]. Treatment of MOLM-14 cells and newly diagnosed and relapsed FLT3-ITD-mutated AML patient–derived cells with quizartinib and azacitidine/decitabine resulted in synergistic growth inhibition.…”
Section: Dna Methylome Modifiers and Their Roles In Flt3-itd Amlmentioning
confidence: 99%
“…Zebrafish have emerged as a powerful model system to study the etiology of hematological malignancies due to their conserved regulation of normal and malignant hematopoiesis, genetic tractability, and established imaging and pharmacologic techniques [6][7][8][9][10][11][12][13]. Expression of known fusion proteins in the myeloid lineage induces the expansion and clustering of myeloid cells in embryos and in cases where embryos survive, malignancy in adults [10,[14][15][16][17][18][19][20][21][22][23][24][25]. Pharmacological inhibitors are effective in preventing the myeloid proliferation and expansion observed in embryos ectopically expressing human fusion proteins [10,23,26].…”
Section: Introductionmentioning
confidence: 99%